Upaya Peningkatan Kompetensi Guru Pendidikan Agama Islam dalam Penggunaan Teknologi Informasi - Zahrotul Millah; Mika Istria; Nurul Latifah; Ni’matul Lathifah; Muhajir Sobirin (IJoIS: Indonesian Journal of Islamic Studies, 2023)
This study aims to determine efforts to increase the competency of Islamic Religious Education teachers in the use of information technology, to determine the success of teacher competence in the use of information technology. The method used in this research is library research. The sources of the literature in this study are obtained from books, journals, magazines, research results (thesis and dissertation), and other sources. After the researcher obtains the relevant literature, then the researchers arranged systematically that would be used in research.The results of this study stated that efforts to increase the competence of teachers would create a better and more efficient quality of the teaching and learning process, from efforts to increase teacher competency it could be seen from the achievement of educational outcomes and goals to improve quality education actively and shape students to be able to learn independently, creatively and innovatively. Besides that participants can learn more confidently according to their own way and have more opportunities to explore because they are motivated by the presence of information technology in the learning process. This can encourage the emergence communication, creativity, and being able to solve the problems faced by students.